STUDI PERBANDINGAN HASIL BELAJAR IPS TERPADU MENGGUNAKAN MEDIA HAND OUT DAN MEDIA ICT - yeni ardila; Teddy Rusman; Nurdin Nurdin (FKIP Unila, 2013)
This research should review about comparative studies of learning outcomes of the IPS integrated use a media hand out and media ICT for student grade VII SMP Negeri 9 Metro Kota Metro for last semester on academic year 2012/2013. The method that used in this study is comparative with ekperimen approach. The population in this study were students of grade VII last semester amounted 192 students for a sample obtained 64 peoples are divided into classes of experimental and control classes. The technique of the sample in this research is a technique clusters random sampling. The technique of the data in this research with obsevation, documentation and test. The testing of hypotheses using t-tes two samples independent.Based on calculations t-tes using formulas separated variance show that thitung (2,019)ttabel (1,999) means the hypothesis research accepted show that learning outcomes of the IPS integrated using a media ICT compared is higher to the analytical study using media hand out.Keywords : learning outcomes, Media Hand Out, Media ICT.